If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 5) * 2 = (2x) * 2 Reorder the terms: (5 + x) * 2 = (2x) * 2 Reorder the terms for easier multiplication: 2(5 + x) = (2x) * 2 (5 * 2 + x * 2) = (2x) * 2 (10 + 2x) = (2x) * 2 Remove parenthesis around (2x) 10 + 2x = 2x * 2 Reorder the terms for easier multiplication: 10 + 2x = 2 * 2x Multiply 2 * 2 10 + 2x = 4x Solving 10 + 2x = 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 10 + 2x + -4x = 4x + -4x Combine like terms: 2x + -4x = -2x 10 + -2x = 4x + -4x Combine like terms: 4x + -4x = 0 10 + -2x = 0 Add '-10' to each side of the equation. 10 + -10 + -2x = 0 + -10 Combine like terms: 10 + -10 = 0 0 + -2x = 0 + -10 -2x = 0 + -10 Combine like terms: 0 + -10 = -10 -2x = -10 Divide each side by '-2'. x = 5 Simplifying x = 5
| -6x-6=7x+33 | | 4(3y+2)=-28 | | -.4x+25=0 | | 3y=155-2x | | 1-3y=3-4y | | 4w-3w+4=-4+7 | | 13x+72= | | a-12+5=-12 | | 6-9n+5n=16-90 | | 9*x=88 | | x+45=6x | | 3(c-2)+8=6+c-4 | | 3x+1=3x+0 | | 2x+3y=155 | | 9.8.2x=96 | | 2z-6z=-25 | | 20=22-d | | -7(9-5a)=-23 | | 3p.9=24 | | -4+3(18-9m)= | | x(x+4)+28=(x-1)(x+8) | | 5=6p-1 | | 2x(3x+x^2)-2x^2=136 | | 5=s-6 | | -(x)whenx=8 | | 63x^2-44x=-5x+60 | | j-20=-23 | | -p+4(3p-2)+5= | | (x*5)+21(1-x)=10 | | 16i+z^2=0 | | 123-95=31y-38y | | 36-4x+8=5+5x-1 |